Measurement of the energy asymmetry in $$t{\bar{t}}j$$ tt¯j production at $$13\,$$ 13 TeV with the ATLAS experiment and interpretation in the SMEFT framework. (Tufts University. Tisch Library., 2022)
Springer Open.